Gaps Along the HIV Care Continuum: Findings Among a Population Seeking Sexual Health Care Services in New York City. (1st July 2018) - Pathela, Preeti; Jamison, Kelly; Braunstein, Sarah L.; Schillinger, Julia A.; Tymejczyk, Olga; Nash, Denis
Abstract : Background: Linkage/relinkage to HIV care for virally unsuppressed people with new sexually transmitted infections is critical for ending the HIV epidemic. We quantified HIV care continuum gaps and viral suppression among HIV-positive patients attending New York City (NYC) sexual health clinics (SHCs). Methods: One thousand six hundred forty-nine HIV-positive patients and a 10% sample of 11, 954 patients with unknown HIV status on clinic visit date (DOV) were matched against the NYC HIV registry. Using registry diagnosis dates, we categorized matched HIV-positive patients as "new-positives" (newly diagnosed on DOV), "recent-positives (diagnosed ⩽90 days before DOV), "prevalent-positives" (diagnosed >90 days before DOV), and "unknown-positives" (previously diagnosed but status unknown to clinic on DOV). We assessed HIV care continuum outcomes before and after DOV for new-positives, prevalent-positives, and unknown-positives using registry laboratory data. Results: In addition to 1626 known HIV-positive patients, 5% of the unknown sample (63/1196) matched to the registry, signifying that approximately 630 additional HIV-positive patients attended SHCs. Of new-positives, 65% were linked to care after DOV. Of prevalent-positives, 66% were in care on DOV; 43% of the out-of-care patients were relinked after DOV. Of unknown-positives, 40% were in care on DOV; 21% of the out-of-care patients relinked after DOV. Viral suppression was achieved by 88% of in-care unknown-positives, 76% in-care prevalent-positives, 50% new-positives, 42% out-of-care prevalent-positives, and 16% out-of-care unknown-positives. Conclusions: Many HIV-positive people, including those with uncontrolled HIV infection, attend SHCs and potentially contribute to HIV spread. However, HIV status often is not known to staff, resulting in missed linkage/relinkage to care opportunities. Better outcomes could be facilitated by real-time ascertainment of HIV status and HIV care status.